Pengukuran Awal Hemipenis Sauria Lamprolepis Smaragdina (Scincidae) dan Lophosaurus Dilophus (Agamidae) - Elisa Secsio Hendra Putra; Keliopas Krey (Igya ser hanjop: Jurnal Pembangunan Berkelanjutan, 2022)
The characteristics of the hemipenis Scincidae and Agamidae New Guinea are veryrarely studied, although they are very easy to do. Morphological characteristics andhemipenis size between these two families are very different. Some have a cylindrical hemipenis that is not lobed to lobed, and some even have a variety of structures withdistinctive ornaments. Tail length can affect the length of the hemipenis. This study aims to describe the characteristics of the hemipenis Scincidae and Agamidae New Guinea. The species Lamprolepis smaragdina and Hypsilurus dilophus were sampledto represent other species in these two families. Preservation of lizard hemipenis refersto research by Zaher and Prudente (2003), Dowling and Savage (1960). Comparison of hemipenis morphology of the two species is very different based on the structure and shape. Hemipenis L. smaragdina is cylindrical and not lobed. The surface structure ofthe hemipenis is smooth and there is no distinctive ornament. While H. dilophus has a cylindrical hemipenis not lobulated with a larger size. The structure is rough, wavy and wider. The results of sample measurements in this study have also become strong evidence that the length of the lizard's tail can affect the length of the hemipenis.